Urban and rural teacher perspectives on Indonesian educational reform: challenges and policy implications - Baharuddin; Burhan (Cogent Education)
Educational reforms rely heavily on teacher engagement and perception, yet limited research has examined how these reforms are received across diverse Indonesian contexts. This study investigates teachers’ perceptions of the Merdeka Belajar policy, focusing on differences between urban and rural settings. A quantitative survey was administered to 581 teachers (336 urban, 245 rural) across eight Indonesian regions, selected through stratified random sampling. A validated Likert-scale instrument measured perceptions of policy implementation, including challenges, support systems, and communication practices. Results indicate that rural teachers were generally more positive toward the reforms but struggled with limited resources (mean score: 4.16) and vague policy directives. Urban teachers reported better access to professional development and teaching materials, yet expressed mixed views on the alignment between reforms and classroom realities. Across both groups, participants highlighted weak communication and insufficient inclusiveness in policymaking. Despite systemic challenges, rural teachers showed notable resilience and adaptability. The study recommends reducing urban-rural disparities through equitable resource distribution, targeted training, and improved stakeholder engagement. Future studies should incorporate qualitative methods and broaden geographic coverage to deepen understanding.